The impact of working capital management on corporate performance among listed manufacturing firms in Malaysia - Nihayatul Azizah Imam Syafii, 1996-, author; Suresh Ramakrishnan, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2018